2021
DOI: 10.3390/jcm10184222
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prognostic Impact of Deranged Liver Blood Tests in COVID-19: Experience from the Regional COVID-19 Center over the Cohort of 3812 Hospitalized Patients

Abstract: Background: Derangement of liver blood tests (LBT) is frequent in patients with Coronavirus disease 2019 (COVID-19). We aimed to evaluate (a) the prevalence of deranged LBT as well as their association with (b) clinical severity at admission and (c) 30-day outcomes among the hospitalized patients with COVID-19. Methods: Consecutive patients with COVID-19 hospitalized in the regional referral center over the 12-month period were included. Clinical severity of COVID-19 at hospital admission and 30-day outcomes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…However, at baseline, only 1% and 0.2% of the patients had LI (i.e., AST>200 IU/L) or AST >400 IU/L, respectively. Thus, in accordance with previous studies [ 10 , 14 , 15 ], we confirmed that liver biochemistry abnormalities in COVID-19 patients are usually mild and predominantly hepatocellular, while AST values are more frequently abnormal than ALT. Nevertheless, no indication for liver dysfunction was observed, since no severe abnormalities in INR were recorded (range 0.7-1.3 in patients not receiving anticoagulants).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, at baseline, only 1% and 0.2% of the patients had LI (i.e., AST>200 IU/L) or AST >400 IU/L, respectively. Thus, in accordance with previous studies [ 10 , 14 , 15 ], we confirmed that liver biochemistry abnormalities in COVID-19 patients are usually mild and predominantly hepatocellular, while AST values are more frequently abnormal than ALT. Nevertheless, no indication for liver dysfunction was observed, since no severe abnormalities in INR were recorded (range 0.7-1.3 in patients not receiving anticoagulants).…”
Section: Discussionsupporting
confidence: 93%
“…In our study we found that baseline AST was associated with poor survival, but this was not confirmed in multivariate analysis. In previous studies [ 7 , 14 , 21 ], abnormal liver biochemical tests have been related with severe course and poor outcome in patients admitted with SARS-CoV-2 infection, reflecting the prognostic impact of liver test abnormalities in this clinical setting. Nevertheless, in our cohort, the patients with abnormal baseline AST (i.e., >40 IU/L) had worse outcomes compared to those with normal AST values (log rank test: chi square: 8.8, P=0.003) ( Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Both parameters are produced in the liver and regulated by IL‑6 promoted inflammation [ 8 ], although CRP is positively affected and albumin negatively affected by this process. These parameters are thus commonly deranged among other liver blood tests during the COVID-19 infection [ 9 ]. The CRP to albumin ratio (CAR) incorporates deviations of these parameters into a single direction and has been shown to be prognostic of more severe disease and higher mortality if elevated in COVID-19 patients [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that these biomarkers provide substantive information about clinical deterioration and the risk of mortality [ 25 , 26 , 38–40 ]. In addition, some studies revealed the role of albumin in COVID-19 prognostication reflecting both possible liver damage, inflammation and the nutritional status of patients [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%